Local Values of Situ Lengkong Conservation Forest to Develop Students’ Green Behavior through History - Ratih, Dewi (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2013)
In this study, the authors will examine how the implementation of local values of Situ Lengkong conservation forest connected with the development of green behavior in SMAN 1 Lumbung into the teaching of history that would be related to our daily life so that the students can understand the local values and knowing that the neighborhood can be a source of learning. Researchers formulate this study into three questions, and there are: what are the local values that related to green behavior in Situ Lengkong conservation forest as a learning source, how the implementation of the history teaching in developing learners’ green behaviors using the Situ Lengkong conservation forest at school, what is the result of history teaching of green behaviors learners utilizing the Situ Lengkong conservation in school. The approach in this study used a qualitative approach with inquiry naturalistic methods. The data collection techniques used in this study were interviews, observation, and documentation study. The results of this study presented that the local values of Situ Lengkong conservation forest certainly related to the development of green behavior and can be used as a source of learning. The teachers have already developed the green behaviors of the Situ Lengkong conservation forest and internalized them in history teaching in SMAN 1 Lumbung. The local values related to the green behavior of Situ Lengkong conservation forest have been actualized in the students’ daily both within the school and in the community